Comparative Analysis of Bank Efficiency in Indonesia, United States, and China Data Envelope Analysis Approach - Putra, Moh. Rizqy Eka; Aji, Tony Seno (PT FORMOSA CENDEKIA GLOBAL, 2024)
The rapid advancement of technology has significantly influenced the financial sector, driving the digitalization of banking, especially post-COVID-19. This study analyzes banking efficiency in Indonesia, the United States (US), and China from 2019–2023 using the Data Envelopment Analysis (DEA) method. Results reveal that US banks maintain the highest and most stable efficiency (average 0.99), followed by China with a positive trend (average 0.98), and Indonesia with stable but slightly lower efficiency (average 0.97). Key findings highlight US efficiency stability, China’s upward trend, and Indonesia’s credit risk management challenges. Recommendations include enhancing risk management in Indonesia, sustaining efficiency in the US, and improving cost efficiency in China.